IMPROVING DECENTRALIZED ECONOMIC GROWTH AND REDUCING ENERGY CONSUMPTION IN THE EUROPEAN UNION WITH THE APPLICATION OF ECOLOGICALLY ORIENTED INNOVATIONS - Natek, Niko; Krajnc, Boštjan (Journal of Energy Technology, 2024)
This article presents applicable approaches for supporting the transition towards sustainable decen- tralized economic development within the European Union, based on the concept of supporting thedevelopment and market uptake of eco-innovations. The main topic addressed is achieving a more effective market uptake of ecologically oriented innovations facilitated through matchmaking, as wellas knowledge and technology transfer between key actors of the innovation process.